HPV na cavidade oral, orofaringe e mama de mulheres com câncer de mama: estudo caso-controle - Pinheiro, Danielle Porto (2023)
Breast cancer (BC) is a public health problem in Brazil and worldwide, with the following main risk factors: heredity, age, alcoholism, reproductive and hormonal aspects, and environmental factors. Human papillomavirus (HPV) is considered a risk cofactor. We investigated the presence of HPV in the oral cavity, oropharynx and breast of women with and without BC. The sample of participants (N = 132) was 58 with BC (case group) and 74 without BC (control group). The oral samples (N = 255) were 130 oral mucosa scrapings and 125 oropharyngeal swabs. Breast samples (N = 215) were collected from 97 participants, 50 case group and 47 control group, obtained from fresh biopsy, mammary papilla punch and mammary duct swab, guided by dermoscopy. HPV detection/genotyping was by multiplex nested PCR with primers that amplified the E6/E7 intergenic region and detected genotypes 6, 11, 16, 18, 31, 33, 45, 52, 56, 58 and 59. HPV DNA was found in 75,8% of samples from the oral cavity and oropharynx and 36,7% of breast samples (p < 0,001). In the case group, the history of cancer in the family was higher (p = 0.015), with gynecological cancer being the most common (p = 0,012). In the association of variables, there was a viral predominance in the age group over 51 years (p = 0,8), in brown (p = 0,015) and evangelical (p = 0,042). In the control group (76,6%) the presence of HPV was higher than in the case group (72%) and in participants who had been to the dentist for more than 6 months (p = 0,021). In oral samples, positivity was similar between case and control groups. The simultaneous presence of more than one genotype was higher in the oral mucosa (p = 0,004). The most relevant result showed that among women with positive HPV in the breast, 78% (28/36) had HPV simultaneously in the oral cavity, oropharynx and breast, and, among them, 42,8% (12/28) had the same genotype in the mouth and breast, with a predominance of 91,6% of HPVs 6 and 11. implementation of screening tests for monitoring susceptible individuals in health services. Furthermore, the same HPV genotypes detected simultaneously in the oral cavity, oropharynx and breast of the same participant is strong evidence that there may, in fact, be an oral contamination pathway for HPV in the breast tissue through the transition zone of the mammary duct through mouth-breast contact, reinforcing the idea of the involvement of HPV as a cofactor of BC.